2016
DOI: 10.1515/bejm-2015-0155
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and the steeplechase between economic activity variables: evidence for G7 countries

Abstract: A sharp increase in unemployment accompanied by a relatively muted response of inflation during the Great Recession and a consecutive inflationless recovery cast further doubts on the very existence of the Phillips curve as a systemic relation between real activity and inflation. With the aid of dynamic model averaging, this paper aims to highlight that this relation resurfaces if (i) inflationary pressures are captured by a richer set of real activity measures, and (ii) one accounts for the existence of a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Consistency of output and inflation in relation to the frequency of the business cycle is in the range of 0.6 to 0.9. Baxa, Plašil, and Vašíček (2013) apply dynamic dynamics modeling (DMA) to confirm the systematic relationship between real activity and inflation. Zhang (2017) transcribes the basic inflation dynamics model as an expanded form of a conventional PC, to which it adds, besides the domestic production gap, also foreign.…”
Section: Summary Of Model Approaches To Estimating Long-term Pcmentioning
confidence: 99%
“…Consistency of output and inflation in relation to the frequency of the business cycle is in the range of 0.6 to 0.9. Baxa, Plašil, and Vašíček (2013) apply dynamic dynamics modeling (DMA) to confirm the systematic relationship between real activity and inflation. Zhang (2017) transcribes the basic inflation dynamics model as an expanded form of a conventional PC, to which it adds, besides the domestic production gap, also foreign.…”
Section: Summary Of Model Approaches To Estimating Long-term Pcmentioning
confidence: 99%
“…The long history of the relationship between inflation and unemployment confirms its applicability to the analysis of economic problems, despite strong criticism of this approach, especially in the last third of the 20th century. The applicability of the Phillips curve (PC) and NAIRU concepts is also supported by authors dealing with the effects of the global recession until 2015 (Gordon, 2013;Coibion and Gorodnichenko, 2015;Rusticelli, 2014;Andrle, Brůha and Solmaz, 2013;Baxa, Plašil and Vašíček, 2013). Further research from 2016 to 2020, examining the aftermath of a global recession, also confirms the functionality of both concepts (Blanchard, 2016;McLeay and Tenreyro, 2019;Zandweghe, 2019, Stock andWatson, 2017;D.…”
Section: Research Results Using the Nairu Concept Pc Since 2013mentioning
confidence: 71%
“…The strong relationship between output and inflation demonstrates the great importance of demand shocks for the euro area economic cycle. Baxa, Plašil and Vašíček (2013) oppose this on data from the USA and the G7 countries in the period from the 1st quarter of 1995 to the 2nd quarter of 2013, when they found that the relationship between economic activity and inflation is relatively robust only when using more complex forms of measurement. Baxa, Plašil and Vašíček (2013) oppose this, when they use data from the USA and the G7 countries in the period from the Q1 1995 to the Q2 2013, when they found that the relationship between economic activity and inflation is relatively strong only when using more complex forms of measurement.…”
Section: Overview Of the Conceptual Framework Of Pc And Nairumentioning
confidence: 96%
“…Baxa, Plašil and Vašíček (2013) oppose this on data from the USA and the G7 countries in the period from the 1st quarter of 1995 to the 2nd quarter of 2013, when they found that the relationship between economic activity and inflation is relatively robust only when using more complex forms of measurement. Baxa, Plašil and Vašíček (2013) oppose this, when they use data from the USA and the G7 countries in the period from the Q1 1995 to the Q2 2013, when they found that the relationship between economic activity and inflation is relatively strong only when using more complex forms of measurement. In the last decade, however, the use of all methods across all countries has weakened this relationship (socalled flattening of the PC), which may be due to structural changes in the economy and monetary policy.…”
Section: Overview Of the Conceptual Framework Of Pc And Nairumentioning
confidence: 96%